2022
DOI: 10.3389/fmicb.2022.828990
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing of Rahnella victoriana JZ-GX1 Provides New Insights Into Molecular and Genetic Mechanisms of Plant Growth Promotion

Abstract: Genomic information for bacteria within the genus Rahnella remains limited. Rahnella sp. JZ-GX1 was previously isolated from the Pinus massoniana rhizosphere in China and shows potential as a plant growth-promoting (PGP) bacterium. In the present work, we combined the GridION Nanopore ONT and Illumina sequencing platforms to obtain the complete genome sequence of strain JZ-GX1, and the application effects of the strain in natural field environment was assessed. The whole genome of Rahnella sp. JZ-GX1 comprised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…L1 also possesses pstABCS genes, representing a prominent transporter system for inorganic phosphorus uptake (Hsieh and Wanner, 2010). Comparable gene clusters have also been reported for phosphonate binding, transport, and degradation in Rahnella victoriana JZ-GX1 and Pantoea agglomerans strain P5 (Shariati et al, 2017;Kong et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…L1 also possesses pstABCS genes, representing a prominent transporter system for inorganic phosphorus uptake (Hsieh and Wanner, 2010). Comparable gene clusters have also been reported for phosphonate binding, transport, and degradation in Rahnella victoriana JZ-GX1 and Pantoea agglomerans strain P5 (Shariati et al, 2017;Kong et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, P. gessardii was recently reported to improve plants' response to Pb-toxicity soils [ 52 ]. Moreover, R. victoriana was recognised as plant pathogen associated with acute oak decline symptoms (also R. variigena ) [ 53 ], causing bacterial canker of Eucalyptus [ 54 ] but recent studies confirmed variety of beneficial features, including IAA production, phosphate solubilization, nitrogen fixation [ 55 ]. Pantoea agglomerans (this bacteria have been detected in immature and mature stigmas, by both methods) was described as plant pathogens and also occurs in plants as an epi- or endophytic symbiont [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…and indirect (antioxidant defence, volatile organic compounds, EPS, etc.) mechanisms to improve plant growth [25,[56][57][58]. The present study investigated the potential direct mechanisms of action in the genome, including IAA synthesis, nitrogen, phosphorus and sulfur transport, metabolism, and degradation, as well as the synthesis of siderophores, polyamines, and GABA, which are beneficial for promoting plant growth.…”
Section: Discussionmentioning
confidence: 99%